Orchestrations of the Malay habitus : Malay food consumption practices in cosmopolitan Singapore - Nurul Dina Amalina Abdulkahar (2015)
Singaporean Malays are frequently depicted as constituting a monolithic, insular and fiercely Muslim ethnic group due to the hard-line multicultural discourse perpetuated by the state prior to the national cosmopolitan project in 1999. This study analyses Malay religiosity and community dynamics in cosmopolitan Singapore by using food consumption practices with family, friends and at work as an indicator. It argues that there has been a continuity of the traditional Malay habitus formulated during Singapore’s nation-building days into cosmopolitan times that explains why a majority of Malays still keep within the boundaries of halal food consumption amongst family, friends and at work. While the research findings confirm this, they also show indications of an emergent elite cosmopolitan Malay habitus brewing amongst some Malays who have chosen to be more lax with halal food consumption amongst friends and at work.